Improving strength and toughness of materials by utilizing spatial variations of the yield stress. (1st January 2017) - Sistaninia, M.; Kolednik, O.
Abstract: The introduction of thin interlayers with low yield stress can greatly improve the strength and the fracture toughness of inherently brittle materials. The reason is that the spatial yield stress variation affects the crack driving force, which strongly decreases when the crack tip is located in the interlayer region, near the boundary to the hard matrix material. This can lead to crack arrest. The material inhomogeneity effect appears without previous delamination of the interlayer. The decisive parameters influencing the effect are the interlayer spacing (the wavelength of the yield stress variation), the interlayer thickness and the yield stress ratio between interlayer and matrix. Based on numerical simulations with the configurational forces concept, it is demonstrated how the architectural parameters of the multilayer must be chosen in order to enhance the fracture stress and the fracture toughness of the material. An iterative procedure is proposed to find the optimum configuration. It is found that the optimum wavelength is inversely proportional to the square of the applied stress. A similar relation is given for composites with spatial variations in Young's modulus. Graphical abstract: Image 1